PENGEMBANGAN VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI IPA TEMA 8 SUBTEMA 1 MANUSIA DAN LINGKUNGAN KELAS V SD NEGERI 50 KOTA TERNATE - Astuti M Saman; Ridwan Jusuf; Eko Purnomo (PEDAGOGIK, 2022)
The purpose of this study is (1) to determine the development process of Video Animation as a ScienceLearning Media Theme 8 sub-theme 1 Humans and the Environment in fifth grade elementary schoolstudents (2) to determine the effectiveness of student learning outcomes on the product of developinganimated videos as a science learning medium. 8 sub themes 1 Human and Environment. This researchis a research and development (R&D) using the 4D (Four-D) development model, namely; definition,design, development, and deployment. The validators who validated the development of this animatedvideo are media experts, science material experts, lesson plans (RPP) experts, and elementary schoolteachers.